Polarisation, accountability, and interstate conflict. (February 2021) - Gallop, Max; Greene, Zachary
Voters constrain democratic leaders' foreign policy decisions. Yet, studies show that elite polarisation restricts the choices available to voters, limiting their ability to punish or reward incumbent governments. Building on a comparative elections and accountability perspective, we hypothesise that the governing context moderates the effectiveness of domestic punishment and reward. The rise of elite polarisation in many democracies undermines voters' ability to sanction leaders through elections. Linking data on international crises to domestic polarisation, we find that leaders are more likely to be involved in the initiation of inter-state disputes, resulting disputes will be more likely to result in prolonged conflict, and ultimately that foreign policy outcomes exhibit greater variance. Results from our analysis and extensive robustness checks demonstrate evidence that increased dispersion of preferences among key actors can lead to extreme and negative foreign policy outcomes as electoral mechanisms fail to reign in and hold governing parties to account.